Strategy for Teaching English in Online Classes During the Covid-19 Pandemic at SMK S Nusantara Tanjung Jabung Timur - ngaisah, iis (English Literature Department, Adab and Humanities Faculty, 2023)
The aim of this research is to find out whether there is a significant effect on teaching strategies using short learning videos accompanied by posters during the pandemic in online classes to improve student learning outcomes. The research subjects were 12 classes of grade XI OTKP students. The method used in this classroom action research is descriptive qualitative, and uses associative problem formulation. The results of the research show that problems in learning can be well handled gradually. The use of short learning videos accompanied by posters during the pandemic in online classes can significantly improve students’ learning outcomes including speaking skills and can increase student activity in learning. This is clearly proven by the comparison of the analysis results in cycle I and cycle II. In cycle I, the individual absorption capacity of each student was 62.08%, with mastery in learning 75%. The results in cycle 2 of completion were achieved by all students with the individual absorption capacity of a student being 80.00% and the classical absorption capacity being 100.00%. This is clearly visible in the absorption capacity of each individual student and can be said to be classically complete. Meanwhile, the level of students' speaking ability consisted of 3 students who are in the excellent category, 6 students who are in the very good category, 3 students in the good category, and student activity increased from 75% to 90%.